Position control of a rodless cylinder in pneumatic servo with actuator saturation - Zhao, Ling; Sun, Jiahui; Yang, Hongjiu; Wang, Tao (ISA transactions, 2019)
In this paper, positioning control of a rodless cylinder in pneumatic servo systems with actuator saturation is investigated via an active disturbance rejection control. A linear extended state observer is designed to estimate and compensate strong friction force and other nonlinearities in the pneumatic rodless cylinder system. An actuator saturation linear feedback control law is developed to further improve the control performance. Furthermore, a linear matrix inequality-based optimization algorithm is employed to estimate a strictly invariance set for the closed-loop system. Experiment results with response time 0.5 s and accuracy 0.005 mm for a 200 mm step signal demonstrate the effectiveness of the proposed control strategy. •An ADRC with actuator saturation is designed for the magnetic rodless cylinder to deal with the internal uncertainties and the external disturbances.•A LMI-based framework is established for the ADRC to enlarge the estimate of the domain of attraction of the pneumatic servo system.•Experiment results illustrate that the proposed controller significantly improves the positioning accuracy by considering the actuator saturation.